The need analysis development of mathematics learning model based realistic mathematical education and literacy in junior high school - Rusdi Rusdi; I Made Arnawa; Ahmad Fauzan; Lufri Lufri (International Conferences on Educational, Social Sciences and Technology)
The research was due to Indonesian students’ literacy in mathematics was unsatisfying according to Programme for International Student Assessment. The aim of this research is to analyze main necessities which grounded the prominence to develop a learning model. This research belongs to descriptive study. Based on data analyzed, the findings reveal that 1) the teachers’ knowledge about mathematical literacy was low, 2) the learning approach still did not related to the material with the context of students’ daily lives, 3) the average value of students' mathematical literacy was 31.87 be classified into low category, and 4) the assessment instruments was far from the mathematical literacy, 5) realistic mathematics education approach ever developed by researchers in learning mathematics has not been combined with the concept of literacy. Based on these findings, the researcher needs to develop mathematics learning model based on realistic mathematical education and literacy in junior high school.